Bleaching color‐loss of green field pea: An investigation on inference of genotypic‐resistance based on chlorophyll and phenolic acid content. Issue 4 (30th September 2020) - McDonald, Linda; Maharjan, Pankaj; Portman, Drew; Panozzo, Joseph
Abstract: Color‐loss of green field pea, commonly referred to as bleaching, can occur prior to harvest once the grain has ripened or during grain storage and is thought to be the result of chlorophyll depletion in the cotyledon. However, the mechanisms of bleaching‐resistance, exhibited within some genotypes, are not well understood. The antioxidant activity of phenolic compounds can inhibit chlorophyll degradation, and therefore, the presence of phenolic compounds may improve bleaching‐resistance. In this study, five green pea genotypes, differing in resistance to bleaching, were assessed for grain‐color as well as content of chlorophyll and major phenolic acids, in both the hull and cotyledon. For each genotype, resistance to bleaching was inferred by the range of color scores observed. Chlorophyll and phenolic acid contents both decreased overall as the whole‐grain color became lighter (bleached); however, there was no direct relation found between these compounds and the known resistance of each genotype. Chlorophyll content in the cotyledon was correlated ( r = −0.735, p < 0.001) with cotyledon color but not with whole‐grain color ( r = −0.212, p = 0.01). Furthermore, the ratio of cotyledon chlorophyll A/B and the ratio of phenolic acid content (hulls) to total chlorophyll content (cotyledon) were not directly correlated with resistance. Although the total chlorophyll and phenolic acid contents were both depleted as the extent of bleaching increased, neither could fully explain differences in bleaching‐resistance between genotypes. Furthermore, the green color and color‐loss of whole‐grain samples could not be fully attributed to chlorophyll pigments. Therefore, it is likely that other phenolic compounds contribute to both the grain color and the resistance to bleaching. Abstract :